The effect of variations in the size of milling balls on the magnetic properties and morphology of natural sand particles in the Rokan River - Afriyunita, Dini; Sinuraya, Salomo; Amiruddin, Erwin; Muhammad, Juandi (Indonesian Physics Communication, 2025)
Magnetic susceptibility, magnetic properties and morphological properties of natural sand from the Rokan river based on variations in milling ball size. Natural sand samples were put into the iron sand separator for separation between magnetic and non-magnetic particles which were then carried out in a ball milling process for 80 hours using iron balls with a diameter of 1, 2, and 3 cm. The results of the ball milling were then separated using NdFeB magnets, these products are called BM I, BM II, and BM III products. The susceptibility values generated in this study increased with increasing milling ball sizes, for milling ball sizes of 1, 2, and 3 cm the magnetic susceptibility values were 12906.293 × 10-5, 13390.387× 10-5, and 14816.736 × 10-5. The results of the VSM test showed that the saturation magnetization obtained by the BM I, BM II, and BM III products was 2.89, 2.28, and 4.71 emu/g, the remanent magnetization values obtained by 0.45, 0.35, and 0.27 emu/g and the coercivity obtained was 249.07, 263.89, and 275.85 Oe. The results of the SEM-EDX identification showed that Fe increased from 16.24% to 22.68%, while in non-magnetic elements Si decreased from 24.49% to 18.76% with an average particle size getting smaller with increasing size milling ball.